SEXUAL AND REPRODUCTIVE EXPERIENCES OF YOUTH WITH DISABILITIES IN ZIMBABWE (African Disability Rights Yearbook, 2021)
Over 120 million youth with disabilities around the world face challenges related to sexual and reproductive health (SRH) services, such as unwanted pregnancy, sexually transmitted infections, and forced abortions and sterilisations. The main causes are cultural, legal, political, and social practices that restrict their rights. Our study explored sexual expectations and experiences of youth with disabilities. We conducted a qualitative study of 20 youth with disabilities using focus group discussions and semi-structured interviews, and then applied a thematic analysis of the data. The findings reveal that youth with disabilities are discriminated against with regard to accessing SRH information. This early exclusion results in discriminatory treatment at other stages of their lives, such as the onset of sexual relationships and marriage. They may also indulge in risky sexual behaviours which expose them to sexually transmitted diseases. Conversely, engaging in relationships, marriage and parenthood brings positive results, especially to women with disabilities. Marrying a non-disabled partner is viewed by disabled men as countering social discrimination. Some of the experiences suggest that parenthood has potential for bringing new status and social capital to persons with disabilities. Our primary recommendations based on this research are that youth-focused SRH schemes need to be redesigned to serve the public health needs of youth with disabilities, a vulnerable population that remains excluded from programming; and girls and women with disabilities should be especially targeted within these redesigned SRH programmes.
Keywords: sexual and reproductive health services; youth with disabilities; discriminatory treatment